A comprehensive test procedure for determination of shear strength parameters of brick masonry specimens - Balasubramanian, S.R.; Rao, K. Balaji; Prasad, A. Meher; Goswami, R. (Journal of Structural Engineering, 2024)
Shear strength is one of the important mechanical properties in the context of estimation of in-plane shear capacity of brick masonry piers or walls. This paper helps to identify the importance of standardization of test procedure and proposes a comprehensive test procedure for carrying out the shear strength test on brick masonry. Based on the identification that, dilatation is an important phenomenon in the shear strength test, a shear testing equipment that is capable for applying pre-compression using gravity is designed, fabricated and got employed in the experimental programme. The value of shear bond strength obtained from the test programme is quite comparable with the results available in the literature. However, for characterizing shear strength of brick masonry, results of the tests adopting a standardised procedure are required. It is also found that, in order to obtain COV of shear bond strength, it is important to carry out tests at more levels of pre-compression, not just three as is prescribed in many international standards.